THE ROLE OF COMMUNICATION IN ENHANCING LEADERSHIP STYLES: CASE STUDIES FROM INDOMARET, ALFAMART, AND SALES TEAMS - Angga Haikal Wahyudi; Muhammad Zul’Asfy Rayhan, Gloria Salsa Br Sembiring, Bunga Nailah Syam, Ermelia Verawaty Hutagalung (ADISAM PUBLISHER, 2025)
Effective communication is a cornerstone of successfulleadership, influencing organizational culture, employeemorale, and overall productivity. This journal exploresthe role of communication in enhancing variousleadership styles, focusing on case studies fromIndomaret and Alfamart, two prominent retail chains inIndonesia, along with insights from sales teams.Through qualitative analysis, including interviews andobservations, this study examines how leaders at theseorganizations utilize communication strategies to fostercollaboration, motivate employees, and navigatechallenges. The findings reveal that leaders whoprioritize transparent, inclusive, and adaptivecommunication not only enhance their leadershipeffectiveness but also cultivate a positive workenvironment that drives team performance. Thisresearch contributes to the understanding of thedynamic interplay between communication andleadership, offering practical recommendations forenhancing leadership practices in retail and beyond